Philosophical Perspectives on Lifelong Learning
XVIII, 334 p.
Keywords: The aim of this book is provide an easily accessible, practical yet scholarly source of information about the international concern for the philosophy, theory, categories and concepts of lifelong learning. The books is concerned to examine in depth the range of philosophical perspectives in the field of lifelong learning theory, policy, practice and applied scholarship, extending the scale and scope of the substantive contribution made by philosophical and theoretical approaches to our understanding of education. The book seeks to make an informed contribution to shaping, expanding and deepening people’s understanding the direction of future developments in educational institutions of all kinds preparing for, providing and delivering lifelong learning in all kinds of formal informal and alternative education institutions, agencies and organizations, and their various approaches, policies, practices and processes in the twenty-first century.